The Investigation of Slang Used by Undergraduate Students on Daily Basis Interaction - Nur Mutmainna Halim; Dahniar Dahniar; Samsidar (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2023)
This study wants to ascertain some slang words and aims of slang used by students in Universitas Islam Makassar. This research applied Patridge's theory (2004) to identify the emergence of slang words and Zhou & Fan’s theory (2013) to find out the functions of slang. This is a descriptive qualitative research. In collecting data, the researchers conducted observation, interviews, and note-taking that considered important during the study. Results of this research found fifteen words of slang that obtained from 10 subjects of this research during the observation. Fifteen words obtained during the observation were baper, salfok, kepeng, kuker, mager, preng, apker, bucin, mehong, mokem, terciduk, anjay, anjrit, kepo, mantul. In addition, from the three functions of slangs were found, pursuit of self-identity was the most found during the interview.